PENGARUH STRES DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN KOJA JAKARTA UTARA - Christie G. Mewengkang (Jurnal Manajemen Pendidikan, 2013)
The objective of this research is to obtain information about the effect of stress and communication on productivity of the principal’s of elementary school. The research was conducted to all of state the principles of elementary school in the district of Koja, the city of North Jakarta by using of survey method with path analysis applied in testing hypothesis. The research concludes: (1). There is direct effect of stress on productivity. (2). There is direct effect of communication on productivity. (3). There is direct effect of stress on communication. Therefore to enhance the principles of elementary schools productivity can be carried out by stress and communication.